Organoids technology in cancer research: from basic applications to advanced ex vivo models - Varinelli, Luca; Illescas, Oscar; Lorenc, Ewelina Julia; Battistessa, Davide; Di Bella, Marzia; Zanutto, Susanna; Gariboldi, Manuela (Frontiers in Cell and Developmental Biology, 2025)
Patient-derived organoids (PDOs) are tridimensional cultures derived from the stem component of a tissue. They preserve the genetic and phenotypic characteristics of the tissue of origin, and represent valuable in vitro models for drug screening, biomarker discovery, cell therapy and genetic modification. Importantly, PDOs reproduce the tumor behavior and can predict therapeutic responses, making them relevant for clinical applications for personalized therapies. PDOs may also be used for studying the interactions between cancer cells and the tumor microenvironment (TME). These interactions are driven by biochemical factors released by the cells, and biomechanical events such as the remodeling of the extracellular matrix (ECM). In recent years, it has become evident that the interactions between cancer cells and the TME have an impact on tumor development and on the efficacy of cancer therapy Therefore, targeting both tumor cells and the TME may improve patient response to treatment. Most PDO culture protocols are limited to epithelial cells. However, recent advances such as use of decellularized ECM (dECM) scaffolds have allowed for the development of in vivo-like environments that host diverse cell types, both normal and pathological, in a tridimensional (3D) manner that closely mimics the complexity of the TME. dECM-based models effectively replicate the interactions between tumor cells, ECM and the microenvironment, are easy to analyze and adaptable for drug testing. By incorporating TME components and therapeutic agents, these models offer an advanced platform for preclinical testing.